2016
DOI: 10.1177/0033688216631203
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Model of Teacher Leadership in ELT: Authentic Leadership in Classroom Practice

Abstract: This study investigates how the model of Authentic Leadership applies to language teaching and its implications for future directions in teacher education programmes. Data was collected from 56 native-speaking English teachers through an online survey consisting of specific open-ended and short answer type questions. The results of the study suggest that currently the concept of classroom leadership is not at the forefront of teachers’ conscious thought, but is, to some extent, embedded in various teaching pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 29 publications
1
38
1
Order By: Relevance
“…Chapter DOI: https://dx.doi.org/10.46679/isbn978819484832502 individuals to think and using the appropriate tools and strategies in the classroom support the development of leadership skills (Cansoy, 2017;Greenier & Whitehead, 2016).…”
Section: This Chapter Is a Part Of The Book 'Innovations In Educationalmentioning
confidence: 99%
“…Chapter DOI: https://dx.doi.org/10.46679/isbn978819484832502 individuals to think and using the appropriate tools and strategies in the classroom support the development of leadership skills (Cansoy, 2017;Greenier & Whitehead, 2016).…”
Section: This Chapter Is a Part Of The Book 'Innovations In Educationalmentioning
confidence: 99%
“…In a survey of school administrators' perspectives on what constitutes good leadership in teachers, Watt, Mills, and Huerta () found that administrators drew particular attention to “classroom environment attributes, such as being an excellent teacher, having great rapport with students, and demonstrating high expectations for students” (p. 57). Others have situated teacher leadership in terms of actions and behaviors carried out in the classroom through teaching and interpersonal interaction with students (see, e.g., Greenier & Whitehead, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the rapid expansion and change in English language teaching (ELT) contexts and the ever‐growing diversity of learners, arguably some of the most essential qualities teachers can possess include a sense of empowerment in their classrooms and schools (Lieberman & Miller, ; McGee, Haworth, & MacIntyre, ) and an understanding of how to appreciate and inspire students as individuals. Thus, it is unsurprising that in recent years there has been increased interest in the topic of leadership in the field, with the hopes of strengthening professionalism by placing more attention on teachers’ evolving roles both inside and outside the classroom (see Christison & Murray, ; Coombe, McCloskey, Stephenson, & Anderson, ; Fenner, ; Greenier & Whitehead, ). This development has led to an emerging discussion about the importance of teacher leadership as an essential component in ELT, with increasing recognition that a focus on fostering understanding and growth of leadership skills can make invaluable contributions to successful teaching and learning (Coombe et al, ).…”
mentioning
confidence: 99%
“…The review performed by them indicated the publication, between 2014 and 2016, of only eight articles in which an exclusively qualitative approach was adopted. The studies aimed at: investigating AL in school environments (Glowacki-Dudka & Griswold, 2016;Greenier & Whitehead, 2016;Shapira-Lishchinsky & Levy-Gazenfrantz, 2015); analyzing gender issues and AL (Liu, Cutcher, & Grant, 2015); proposing AL for specific environments such as strategic planning (Rhine, 2015); analyzing paradoxes of authenticity in the practice of leadership (Nyberg & Sveningsson, 2014); and analyzing AL in nursing practices (Shapira-Lishchinsky, 2014; Waite, McKinney, Smith-Glasgow, & Meloy, 2014). None of the studies, therefore, investigated the congruence between the leader's discourse and the AL theory, aiming to enlarge it and/or contribute to its consolidation.…”
Section: Liderazgo Auténtico: Un Análisis Temático Teórico Del Discurmentioning
confidence: 99%